2018
DOI: 10.1111/jonm.12715
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial safety climate, workplace violence and self‐rated health: A multi‐level study among hospital nurses

Abstract: Psychosocial safety climate should be evaluated and promoted to prevent workplace violence in nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
(85 reference statements)
3
40
1
Order By: Relevance
“…However, the interview results from both Germany and Sweden showed the intended shift of referent did not work as well as desired, and this challenge was not solved by rewording items. This finding based on our qualitative study is somewhat in contrast to results from a number of quantitative survey studies that have found psychometric support for aggregating individual level responses to a meaningful group score for PSC (see e.g., Dollard & Bakker, 2010;Idris & Dollard, 2014;Law et al, 2011;Pien et al, 2018). However, even in those studies, the majority of variance can be attributed to the individual level, and previous research on workplace social capital items has also demonstrated the intended shift of referent can be a cognitively complicated task (Berthelsen et al, 2016).…”
Section: Psc As a Group Constructcontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the interview results from both Germany and Sweden showed the intended shift of referent did not work as well as desired, and this challenge was not solved by rewording items. This finding based on our qualitative study is somewhat in contrast to results from a number of quantitative survey studies that have found psychometric support for aggregating individual level responses to a meaningful group score for PSC (see e.g., Dollard & Bakker, 2010;Idris & Dollard, 2014;Law et al, 2011;Pien et al, 2018). However, even in those studies, the majority of variance can be attributed to the individual level, and previous research on workplace social capital items has also demonstrated the intended shift of referent can be a cognitively complicated task (Berthelsen et al, 2016).…”
Section: Psc As a Group Constructcontrasting
confidence: 99%
“…This leads to a relevant consideration about how many items are actually required for a valid measurement of a construct. Findings from confirmatory factor analyses support the construct validity of the theoretically based four-factor structure measured by the 12-item version of PSC (Hall et al, 2010;Pien et al, 2018). Despite the theoretical reasoning behind the PSC measure, it seems data most often are collapsed into one single composite PSC score (see e.g., Afsharian et al, 2018;Biron et al, 2018;Bronkhorst, 2015;Idris et al, 2015;Potter et al, 2017).…”
Section: Length and Format Of The Psc Instrumentmentioning
confidence: 79%
See 1 more Smart Citation
“…[5] In China, the Chinese version of the Psychosocial Safety Climate Scale or PSC-12 recommended the need to promote safety classes and trainings among nurses to minimize workplace violence or at least nurses will become more equipped in intervening such workplace events. [15] Violence may occur, anywhere and anytime and no one is ever safe from experiencing it. Mental health nurses in particular work and provide care for people who may have experienced the worst form of violence at least once in their lifetime leading to their commitment in the mental health facility.…”
Section: Discussionmentioning
confidence: 99%
“…These factors were seen among the patients who commit violence against nurses more often than other patients. [15]…”
Section: Incidence and Prevalencementioning
confidence: 99%